High-sensitivity troponin I as a predictor of left ventricular dysfunction in the use of cardiotoxic anticancer agents for breast cancer in patients with predominantly low and moderate risk of cardiotoxicity - V. D. Levina; M. G. Poltavskaya; P. Sh. Chomakhidze; A. A. Meshcheryakov; L. V. Bolotina; T. I. Deshkina; D. S. Valiulina; A. N. Gerasimov; O. V. Andreeva; A. A. Shmeleva; Z.Z.A. Fashafsha; A. R. Levshina; et al. (Российский кардиологический журнал)
Aim. To study the significance of monitoring high-sensitivity troponin I (hs-cTnI) for predicting anthracycline-induced left ventricular (LV) dysfunction in the treatment of breast cancer in patients with moderate and low risk of cardiotoxicity (CT).Material and methods. The study involved 49 patients with breast cancer aged 50±10 years who underwent neoadjuvant or adjuvant chemotherapy, which included doxorubicin at a course dose of 60 mg/m2 and an average cumulative dose of 251±60 mg/m2. The level of hs-cTnI was determined by an ultrasensitive method before the start of chemotherapy, after each course of anthracyclines and in 18 patients before the administration of anthracyclines. The level of hscTnI >0,017 ng/ml was considered elevated. Echocardiography was performed before the start of chemotherapy, after the end of anthracycline therapy, and every 3 months for 12 months thereafter. CT was defined as a decrease in LV ejection fraction (EF) by ≥10% to <53%.Results. CT risk before chemotherapy was considered low and moderate in 96% of patients. An increase in hs-сTnI was detected ≥1 times in 56,8% of patients: before chemotherapy — in 13,5%, after 1 and 2 courses of anthracycline therapy — in 13,9%, after 3, 4, 5 and 6 courses — in 44%, 62%, 71% and 66% of patients, respectively. The levels of hs-cTnI before and after administration of anthracyclines did not differ significantly. The development of LV dysfunction was observed in 16,3% of patients. There were following prognostic significance of an increase in hs-cTnI at any time of chemotherapy for a decrease in LV EF: sensitivity — 87,5%, specificity — 50%, the positive predictive value — 28%, the negative predictive value — 94,7%. The closest relationship was noted between CT and hs-cTnI value before the start of chemotherapy (β=0,45, p=0,005) and after the 3rd course of anthracycline therapy (β=0,56, p=0,002).Conclusion. An increase in hs-cTnI level before and during anthracycline thera py in patients with a low risk of cardiotoxicity has a prognostic value in relation to the development of left ventricular dysfunction. Hs-cTnI assessment should be performed before the start of therapy, and then starting from the 3rd course of anthracycline therapy in all patients, regardless of the risk of cardiotoxicity.